0302 NOCTURNAL BLOOD PRESSURE AND HEART RATE IN NORMOTENSIVE INSOMNIA PATIENTS. (28th April 2017) - Lamy, M; Jarrin, DC; Ivers, H; Morin, CM
Abstract: Introduction: While sleep-wake cycles are known to affect cardiovascular functions, there is little information on nocturnal blood pressure (BP) and heart rate (HR) in patients with chronic insomnia. Given that insomnia is a risk factor for hypertension, the aim of the present study was to explore BP and HR patterns over the course of the night in normotensive patients with chronic insomnia. Methods: Fourteen adults (Mage  = 37.5 ± 12.3 years old; 71.4% women, IMC = 24.2 ± 4.9) with chronic insomnia participated in this study. They underwent two nights of baseline ambulatory polysomnography (PSG) using standard montage. In addition, pulse transit time (PTT) and EKG beat-to-beat measures via three-lead EKG were measured continuously throughout the night to obtain blood pressure (systolic and diastolic; SBP, DBP) and HR, respectively. Using data from the second PSG night, sleep was visually scored (WAKE, N1, N2, N3 and REM) and divided into three sleep periods (first, middle, last) throughout the night. Results: The lowest DBP and SBP values were observed during N2 compared to other sleep stages (mean DBP: 72.2 vs 72.7–75.2, p<.0001; mean SBP: 113.9 vs 115–116.5, p =.01), and during the last sleep period (DBP 71.5 vs 72.8–74.5; p=.0007; SBP 112.4 vs113.6–116.9; p=.004). SBP was also significantly reduced in N3 during the middle sleep period (111.5 vs 112.8–115.3, p=.003). Similarly, HR was lowest during N2 (62.6 vs 64.4–69.0, p<.0001), especially during the middle sleep period (63.2 vs 65.1–67.5, p =.004). HR during REM sleep was lower during the late compared to early sleep periods (63.3 vs 65.4–66.9, p=0.02). Conclusion: The lowest values for BP and HR were obtained during N2, particularly during the last sleep period. This pattern of sleep-related cardiovascular changes is different from that typically observed in good sleepers, which may suggest increased sympathetic activation during the earlier part of the night among individuals with chronic insomnia. Additional studies are needed to examine blood pressure and heart rate changes during sleep in order to document further the long-term cardiovascular risks associated with chronic insomnia. Support (If Any): Canadian Institutes of Health Research (MOP42504) and Fonds de recherche du Québec - Santé (32207).